Public Participation in the Law-Making Process in Indonesia - Wardana, Dodi Jaya; Sukardi, Sukardi; Salman, Radian (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Participation from the general public is an essential component that must be taken into account during the legislative process. It is essential to the operation of laws in a country and includes the participation of society in the legislative process. This is particularly important in terms of the rule of law, the hierarchy of legal norms, and the operation of the law in its entirety. The purpose of this research is to evaluate the significance of public participation in the legislative process in Indonesia as well as the potential repercussions of excluding this procedure from the legislative process. For the purpose of carrying out this research, normative legal research that takes both a statutory and conceptual strategy was utilized. According to the findings, public participation offers a variety of possibilities for involvement, in accordance with the requirements of Article 96 of Law Number 11 of 2012 on the Formation of Regulations (UU P3). Due to this, the importance of public participation cannot be overstated, despite the restricted channels through which members of the public can communicate their thoughts and goals.